A heterodox Marxist and his century: Lelio Basso selected writings - Basso, Lelio 1903-1978 (Brill, 2021)
"Lelio Basso was a major thinker and political leader of Italian socialism; his writings are here presented for the first time in English translation. They document his anti-fascist work from the 1920s to the 1940s, his short-lived leadership of the Socialist Party, his internationalist work in the 1970s, his rediscovery of Rosa Luxemburg and renewal of Marxist thinking. The texts collected in this book provide an original contribution to the renewal of Marxism in Europe and an example of political practice rooted in mass mobilisation and international solidarity, with major lessons for the contemporary left"
Keywords: Basso, Lelio -- 1903-1978; Politische Philosophie; Socialism / Italy / History / 20th century; Socialism; Italy; 1900-1999; History